2001
DOI: 10.1128/aac.45.4.1058-1064.2001
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Deformylase as an Antibacterial Drug Target: Target Validation and Resistance Development

Abstract: New inhibitors of peptide deformylase (PDF) which are very potent against the isolated enzyme and show a certain degree of antibacterial activity have recently been synthesized by our group. Several lines of experimental evidence indicate that these inhibitors indeed interfere with the target enzyme in the bacterial cell. (i) The inhibition of Escherichia coli growth could be counteracted by overexpression of PDF from different organisms, including E. coli, Streptococcus pneumoniae, and Haemophilus influenzae.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 28 publications
(22 reference statements)
3
81
1
Order By: Relevance
“…Actinonin is synthesized by actinomycetes (4), and it inhibits bacterial growth in a bacteriostatic manner (5,6). Unlike protein synthesis in eukaryotes, where translation is initiated with a nonformylated methionyl (Met) initiator tRNA (tRNAi), most eubacteria initiate translation with a formylated Met-tRNAi (5,7).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Actinonin is synthesized by actinomycetes (4), and it inhibits bacterial growth in a bacteriostatic manner (5,6). Unlike protein synthesis in eukaryotes, where translation is initiated with a nonformylated methionyl (Met) initiator tRNA (tRNAi), most eubacteria initiate translation with a formylated Met-tRNAi (5,7).…”
mentioning
confidence: 99%
“…The most common, previously identified mutations causing actinonin resistance are loss-of-function mutations in the fmt gene (2,5). This gene encodes methionyl-tRNA formyltransferase (FMT), an enzyme that adds the formyl group to the Met-tRNAi.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Over-expression of FabB protein appeared to lead to increased resistance to thiolactomycin in E. coli [40]. Apfel and colleagues [41] demonstrated that over-expression of peptide deformylase in a cell reduced its susceptibility to inhibitors specific for the essential target, peptide deformylase.…”
Section: Discussionmentioning
confidence: 99%